2008
DOI: 10.1086/524105
|View full text |Cite
|
Sign up to set email alerts
|

NGC 346 in the Small Magellanic Cloud. III. Recent Star Formation and Stellar Clustering Properties in the Bright HiiRegion N66

Abstract: In the third part of our photometric study of the star-forming region NGC 346/ N66 and its surrounding field in the Small Magellanic Cloud (SMC), we focus on the large number of low-mass pre-main-sequence (PMS) stars revealed by the Hubble Space Telescope observations with the Advanced Camera for Surveys. We investigate the origin of the observed broadening of the PMS population in the V À I; V color-magnitude diagram. The most likely explanations are either the presence of differential reddening or an age spr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 52 publications
(113 reference statements)
5
93
1
Order By: Relevance
“…Their large number may have introduced biases. Hennekemper et al (2008) report numerous premain-sequence T Tauri stars, which are unfortunately too faint (see Fig. 4) to be detected by the present study.…”
Section: A3 Ngc 346contrasting
confidence: 68%
See 3 more Smart Citations
“…Their large number may have introduced biases. Hennekemper et al (2008) report numerous premain-sequence T Tauri stars, which are unfortunately too faint (see Fig. 4) to be detected by the present study.…”
Section: A3 Ngc 346contrasting
confidence: 68%
“…However, Nota et al (2006) found several populations with different ages: 4.5 Gyr for stars in the field, a young population with ages ranging from 3 to 5 Myr, in which stars with a mass less than 3 M are still pre-main sequence stars, and a population with an intermediate age of 150 Myr. In this open cluster and in its vicinity, we found 55 emissionline stars. Dereddening with a global value of 0.008 mag for massive stars from Hennekemper et al (2008) suggests that most of them are on the main sequence. The spectral classification obtained differs on average by 1 spectral subtype for the 12 stars shared with spectral classifications by other authors.…”
Section: A3 Ngc 346mentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the ages based on PMS isochrones are 1.5-2.0 times shorter than the "nuclear" MSTO ages. However, our PMS age is mostly based on the TOn luminosity, and not on the PMS stars, whose color is affected by several uncertainties (see e.g., Hennekemper et al 2008). Another possible source of error is the use of different sets of models to study different phases: we do not have this kind of problem because in this work we used the PARSEC models which follow the entire evolution from the PMS to the post-MS. Figure 10 shows the synthetic LF (blue line) corresponding to the best SFH compared with the observed counterpart (red line).…”
Section: Quantitative Derivation Of H301ʼs Sfhmentioning
confidence: 99%